A Quantitative and Qualitative Study of Notes Left by Youth Who Died by Suicide in Quebec from 1895 to 1985. Issue 4 (1st October 2020) - Ligier, Fabienne; Michaud, Laurent; Kabuth, Bernard; Lesage, Alain; Corriveau, Patrice; Séguin, Monique
Abstract : The study of suicide notes and the evolution of their content could contribute to a better understanding of reasons conducive to suicide mortality and offer further prevention strategies. From 1895 to 1985, 706 coroner's inquests of individuals who died by suicide and were 20 years old or younger were found in the province of Quebec. Quantitative analysis compared those who left notes ( n  = 47) to those who did not leave notes ( n =  659). Furthermore, notes were subjected to inductive thematic analysis. Sociodemographic characteristics of the deceased individuals did not change over time. Qualitative analysis revealed four superordinate themes: (1) last wishes, (2) to those I leave behind, (3) about me and how and why I did it, and (4) self-positioning in the world . Only the last theme evolved over the time period considered. Suicide notes shed light on the psychological state of the majority of young note leavers and suggest the persistent feelings of distress and entrapment before the suicide, which may be important factors for caregivers and family members to monitor.